1992
DOI: 10.1002/mrd.1080330317
|View full text |Cite
|
Sign up to set email alerts
|

Automated analysis of rabbit sperm motility and the effect of chemicals on sperm motion parameters

Abstract: Appropriate software settings and optimum procedures were determined for the measurement of the motion parameters of rabbit spermatozoa by the CellSoft (Cryo Resources Ltd., Montgomery, NY) computer-assisted digital image analysis system. The system was used to follow motion parameter changes occurring in spermatozoa incubated for 6 hr with or without exposure to chemicals. Mean amplitude of lateral head displacement (AALH) increased over the 6 hr period, while curvilinear velocity (Vc) first increased and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…3) (32,33) and humans (34). Other studies have confirmed that the determination of sperm kinematics by CASA systems is a useful tool in the evaluation of toxicological effects in studies using animal models (29,31). The kinematics of flagellar bending are not constant throughout the lifespan of the sperm cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3) (32,33) and humans (34). Other studies have confirmed that the determination of sperm kinematics by CASA systems is a useful tool in the evaluation of toxicological effects in studies using animal models (29,31). The kinematics of flagellar bending are not constant throughout the lifespan of the sperm cells.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, simple evaluation of sperm motility by Computer Assisted Semen Analysis (CASA) systems (28,29) or together with other tests (30,31) is today a widely used practice for the assessment of the effects of toxicants on sperm function because it allows objective data to be obtained and permits the detection of small but significant changes induced in sperm motion (29,30).…”
mentioning
confidence: 99%
“…Table 1 summarizes the range of in vitro and in vivo bioassays currently available for reprotoxicity testing of ART products. These reprotoxicity bioassays test the possible negative influence on the reproductive mechanisms and processes like maturation, motility, and fertilization of mammalian spermatozoa and oocytes of mice, hamsters, rabbits, and bovine (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Exposed mouse embryos are being cultured in vitro or transplanted in vivo to test their developmental potential (14,18).…”
mentioning
confidence: 99%
“…Ejaculates were collected from rabbits with an artificial vagina and seminal contaminants removed by centrifugation (500 x g , 10 min) through a discontinuous Percoll gradient (90%:65%:50%) as previously described (Young et al, 1992). Sperm, free of seminal plasma contaminants, were resuspended in medium M. A suspension of washed sperm in medium M (0.5-1 x 107/ml) alone, or together with the chlorides of either lead, zinc, cadmium, and mercury, or potassium dichromate, was incubated in a 13 x 75 mm glass culture tube (final volume 1 ml) at 37°C in air.…”
Section: Incubation Of Spermmentioning
confidence: 99%